Sinergi Kepemimpinan dan Literasi: Upaya Kepala Sekolah dalam Mengembangkan Perpustakaan Sekolah - Binti Masrufa; Mihmidaty Ya’cub; Ananda Desi Ramandani (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2024)
This research analyzes the principal's strategy for developing the library at SMPN 5 Jombang. The research method is descriptive qualitative, with data collection techniques conducted through interviews, observation, and documentation. The research subjects consisted of the school principal, the head of the library, and class VIII students. The results of the research show that the principal of SMPN 5 Jombang implemented four strategies in developing the library, namely the strategy of advising by forming a library organization, the strategy of reprimanding indirectly through curriculum waka, the strategy of appreciating by giving praise and appreciation, and the strategy of receiving suggestions through coordination meetings. Apart from that, the school principal also makes efforts to develop library management, including completing collections, improving the spatial layout, improving services, increasing interest in reading through library programs, and supervising through annual evaluations. The results of this research reinforce the critical role of school principals in developing libraries as a vital means of supporting learning. Library development requires commitment and active participation from all school members, as well as continuous efforts to optimize library functions to support improving the quality of learning and achieving educational goals in schools.